Round table discussion TNBs Perspective on Supporting Sustainable Program in Malaysia - Muhammad Aizat, Azed (2022)
PEKAN, 28 December 2021 – Malaysian Sustainable University Campus Network Universiti Malaysia Pahang (MYSUN-UMP), in collaboration with Unit Lestari UMP, convened the second series of a round-table discussion with industry, TNB Renewables Sdn. Bhd., with the topic “TNB’s Perspective on Supporting Sustainable Program in Malaysia” delivered by the Managing Director of TNB Renewables Sdn. Bhd., Ir. Mohd Yusrizal Mohd Yusof.